US intelligence and Al Qaeda : analysis by contrasting narratives - Werd, Peter de (Edinburgh University Press, 2020)
This book sets out a new analytic methodology: analysis by contrasting narratives (ACN), which states that defining an enemy and attempting to counter threats can contribute to the manifestation of that threat. Peter de Werd applies ACN to the problem the US faced in understanding and responding to the phenomenon of Al Qaeda in the 1990s.